ENGLISH VOCABULARY AND GRAMMAR PROFICIENCIES OF SMPN 17 STUDENTS IN BENGKULU CITY - Reza Muhamad; Zahrida; Mukhrizal; Erni Sukesi (UNIB Press, 2023)
The objectives of this research were to find out “how the student’s English vocabulary and grammar proficiencies were” . The population was all students of SMP N 17 Bengkulu City. The samples were approximately 57 students, with detail were 4 classes of 7th grade. The design of the research was descriptive quantitative. The instrument was English grammar and vocabulary test to measure students’ skill. The results of the research showed that the total average score from grade 7th, their total average score was 33, their average vocabulary score was 20 and then their average grammar score was 44. Based on the results, it can be concluded that the 7th grade students’ vocabulary and grammar skills of SMPN 17 Bengkulu City were still low, also the difference between their average grammar and vocabularyscores of grade 7 was very far, but both’s scores were still under the minimum score (75). This phenomenon could have been prevented if junior high school students had received English background knowledge when they were still in elementary school.This phenomenon is what the researchers are trying to show that this is the effect of not getting background knowledge of English when they were in elementary school. Of course this will cause problems for these students in the future, because the level of difficulty in terms of English study they will encounter in the future will be more difficult.